Dakwah Jamaah Tabligh di Asia Tenggara; Negosiasi Mazhab, Transformasi Pendidikan dan Fasilitator Konflik Politik-Keagamaan - Hamdi, Saipul (Jurnal Review Politik, 2021)
Mazhab was not the fundamental and central discourse in Tablighi Jamaat (TJ) communities. It is in the opposite position where mazhab discourses have been isolated and marginalized within the TJ broader dawah material context. TJ figures accused and claimed mazhab as the primary source of conflict and division that hindered progression and global interaction among Muslim groups. Thus, mazhab was fluid and negotiable in JT dawah and ritual activities, particularly when the members of TJ in a dawah camp program (khuruj). As a result, TJ has a good position and image in the community and less rejection and resistance by other communities than Ikhwanul Muslimin or Hizbut Tahrir. However, the choice of ignoring mazhab discourses emerges a social stigma and judgment to Tabligi as the group that does not fully understand Islam. The article aims to understand the phenomena of practicing mazhab in the TJ community in Southeast Asia, particularly in Thailand, Malaysia, and Indonesia. The article also investigates the mazhab negotiation between TJ members and local people where the dawah occurs in a specific context. The article also looks at changes in religious educational program developed by TJ members that tend to be informal religious education. The majority of informal religious education surrounding JT communities is tahfiz school (memorizing the Quran). TJ members are more interested in sending their children to tahfiz school than informal school and later become Islamic priests (kyai). They are not interested to see their children take the university level. Besides, the article also concerns exploring another role of TJ in a socio-political context where they become facilitators to overcome the Pattani Muslim conflict with the Thai government.